2006
DOI: 10.1111/j.1463-5224.2006.00478.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical properties of ocular adenomas, adenocarcinomas and medulloepitheliomas

Abstract: A Senior Honors Thesis:Presented in partial fulfillment of the requirements for graduation with distinction in Zoology in the undergraduate college of Arts and Sciences of The Ohio State University. By Abstract:Ocular medulloepitheliomas, adenomas and adenocarcinomas share a common phenotype and originate from the cells of the ciliary epithelium. This can make it very difficult to differentiate between these tumors histopathologically. Therefore, this study focused on identifying a combination of immunologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 43 publications
1
26
1
Order By: Relevance
“…Mimicking normal neuroepithelium, iridociliary adenomas are immunoreactive for vimentin and neuron‐specific enolase (NSE) with variable immunopositivity for S100, glial fibrillary acidic protein (GFAP), and desmin. There is also immunoreaction to telomerase reverse transcriptase (TERT), and some neoplasms express cytokeratins …”
Section: Intraocular Neoplasiamentioning
confidence: 99%
See 1 more Smart Citation
“…Mimicking normal neuroepithelium, iridociliary adenomas are immunoreactive for vimentin and neuron‐specific enolase (NSE) with variable immunopositivity for S100, glial fibrillary acidic protein (GFAP), and desmin. There is also immunoreaction to telomerase reverse transcriptase (TERT), and some neoplasms express cytokeratins …”
Section: Intraocular Neoplasiamentioning
confidence: 99%
“…Iridociliary adenocarcinomas are immunoreactive for vimentin, NSE and TERT with variable immunopositivity for S100, cytokeratin, GFAP and desmin. Malignant iridociliary neoplasms have increased TERT expression and are more likely to express cytokeratin than benign tumors …”
Section: Intraocular Neoplasiamentioning
confidence: 99%
“…Immunohistochemistry showed that citokeratin AE1 and citokeratin AE3 were more consistently expressed in adenocarcinomas and less frequently in the adenomas, whereas none of the tumor types were positive for citokeratin 7. In regard to aggressiveness, an inverse expression pattern was seen to citokeratin 20 (decreased in adenocarcinomas and increased in adenomas) and telomerase reverse transcriptase (increased in adenocarcinomas and decreased in adenomas) (KLOSTERMAN et al, 2006).…”
Section: Adenomas and Adenocarcinomasmentioning
confidence: 98%
“…Masses display different patterns of pigmentation and invasiveness, are solid or pedunculated (KLOSTERMAN et al, 2006), and usually arise from the nonpigmentated epithelium of the ciliary body (WILLIS & WILKIE, 2001). Golden Retriever and Retriever Labradors have been reported as predisposed breeds (WILLIS & WILKIE, 2001).…”
Section: Adenomas and Adenocarcinomasmentioning
confidence: 99%
“…This rare congenital embryonic tumor is reported in pediatric or young human patients. 1,14,19,31 Medulloepithelioma is a very rare tumor in dogs 2,8,15,26 and horses, 18 and is extremely rare in cats. 12 Isolated cases have been reported in other species, including birds 5 and llamas.…”
mentioning
confidence: 99%